Pemberdayaan PUS Untuk Menjadi Akseptor KB Aktif Guna Menciptakan Keluarga Yang Berkualitas di Desa Sirambas Kecamatan Panyabungan Barat Kabupaten Mandailing Natal - Nasution, Helmi Wardah (Cattleya Darmaya Fortuna, 2022)
Every human being has the same obligations and rights, but in reality there are changesin equality of obligations and rights between women and men. Most of the time the differences are visibleThe real difference between women and men is in societies that adhere to a patriarchal culture, including the stateIndonesia. In a patriarchal society, women are in a powerless position because they are lackingthere is no opportunity for women to make decisions in their lives, including taking decisionsdecisions regarding him.Apart from the less favorable role of women in making decisions to becomefamily planning acceptors, women's powerlessness in the family can also be seen from the difficulty of women doing itactivities outside the family. So there is a need for activities that can reduce inequality between womenboth in the family and society. The KB (Family Planning) program can be used as one of the programswhich is expected to increase women's empowerment. Based on the background above, formulaThe problem in this service is